Association between duration of progesterone supplementation and clinical outcomes in artificial frozen-thawed embryo transfer cycles - Liu, Ling; Zhou, Hongyan; Hu, Jie; Sun, Xingyu; Liu, Doudou; Huang, Guiying (Frontiers in Endocrinology, 2023)
Background: Progesterone administration before transfer in hormone replacement treatment (HRT) is crucial for the clinical outcomes of frozen-thawed embryo transfer (FET), but the optimal duration of progesterone remains controversial. This study aimed to investigate the effect of the duration of progesterone administration on the clinical outcomes of FET cycles.Methods: This study included 353 artificial FET cycles conducted at a reproductive medicine center between April and October 2021. The FET cycles were stratified into four groups based on the duration of progesterone supplementation before the procedure and the embryonic development stage: group P3 (73 patients) received intramuscular progesterone for 3 days and group P4 (87 patients) for 4 days before Day 3 frozen embryo transfer, group P5 (70 patients) for 5 days and group P6 (123 patients) for 6 days before frozen blastocyst transfer. This trial was performed using one or two vitrified embryo(s) when the endometrial thickness reached 7 mm after oestrogen supplementation in an artificial cycle. The primary outcome was clinical pregnancy, and secondary outcomes included biochemical pregnancy, implantation, early pregnancy loss, and live births.Results: There were no significant differences in the demographic and clinical characteristics between the groups. No significant difference was observed in the clinical pregnancy rates between groups: 23/73 (31.5%) in group P3 vs 28/87 (32.2%) in group P4 (P = 0.927). Compared to group P5 (41/70, 58.6%), the clinical pregnancy rate was not significantly different in group P6 (77/123, 62.6%, P = 0.753).There was no significant difference in the implantation rates between groups: 33/136 (24.3%) in group P3 vs 34/166 (20.5%) in group P4 (P = 0.431), and 62/133 (46.6%) in group P5 vs 107/231 (46.3%) in group P6 (P = 0.956). The duration of progesterone supplementation (mean: 3.5 ± 0.5 days; range:3-4 days) before Day 3 frozen embryo transfer did not impact clinical pregnancy (odds ratio [OR] 1.048; 95% confidence interval [CI], 0.518-2.119). The duration of progesterone administration (range:5–6 days) before frozen blastocyst transfer may not affect clinical pregnancy (OR 1.339; 95% CI, 0.717-2.497).There may be no significant correlation between the duration of progesterone supplementation and pregnancy outcomes in artificial FET cycles.